Radio Continuum Halos of Seven Nearby Large Galaxies Using uGMRT - Souvik Manna; Subhashis Roy; Tapas Baug (The Astrophysical Journal, 2024)
We present the results of deep radio observations of seven nearby large galaxies observed using the upgraded Giant Metrewave Radio Telescope (uGMRT) 0.3–0.5 GHz receivers with an angular resolution of ∼10″. The achieved sensitivities of these observations range from ≈15 to 50 μ Jy beam ^−1 , which is a factor of ≈3–4 lower than the previous observations at these frequencies. For two galaxies (NGC 3344 and NGC 3627) with moderate inclination angles, significant diffuse emissions are seen for the first time. The detected radio halos in the vertical direction are significantly larger in our 0.4 GHz maps compared to the observations at ∼1.5 GHz for four nearly edge-on galaxies—NGC 3623, NGC 4096, NGC 4594, and NGC 4631. For these four galaxies, significantly larger halos are also detected along the galaxy disk. For NGC 3623 and NGC 4594, we could detect elongated radio disks that were not seen before. We also present new uGMRT images of NGC 3344 and NGC 3623 at 1.3 GHz and a new VLA image of NGC 3627 at 1.5 GHz. We fitted an exponential function to the flux densities along different cross-cuts and found a significantly wider distribution at the 0.4 GHz uGMRT images compared to the high-frequency images at ∼1.5 GHz. Using maps at 0.144, 0.4, and ∼1.5 GHz, we made spectral index maps of the seven sample galaxies and found a steepening of the spectrum up to a value of ∼−1.5 in the halo regions of the galaxies.